Neonatal and Maternal 25-OH Vitamin D Serum Levels in Neonates with Early-Onset Sepsis - Gamal, Taha Soliman (Children (Basel), 2017)
Vitamin D is a fat-soluble vitamin that is important for calcium metabolism and plays an important role in the immune functions. The aim of this study was to measure neonatal and maternal 25-OH vitamin D serum levels in neonates with early onset sepsis. The study included fifty neonates with early onset sepsis (25 full-term and 25 preterm infants) and thirty age and sex matched healthy neonates as controls. After history taking and clinical examination, complete blood count, C-reactive protein and 25-OH vitamin D serum levels (neonatal and maternal) were measured for all neonates. The mean gestational age for neonates with sepsis was (37.5 ± 0.98 for full term and 34.1 ± 1.26 for preterm neonates). Neonatal and maternal 25-OH vitamin D serum levels were significantly lower in patients (6.4 ± 1.8 and 24.6 ± 2.2 nmol/L) than controls (42.5 ± 20.7 and 50.4 ± 21.4 nmol/L). Significant negative correlations between neonatal and maternal 25-OH vitamin D serum levels and all sepsis markers and significant positive correlations between neonatal and maternal 25-OH vitamin D levels were present. At cut-off values <20 nmol/L for neonatal and <42 nmol/L for maternal 25-OH vitamin D for detection of neonatal sepsis, the sensitivity, specificity, positive predicted value (PPV) and negative predicted value (NPV) were 84%, 79%, 94.7% and 82.3% for neonatal and 82%, 77%, 91.4% and 80.6% for maternal 25-OH vitamin D, respectively. Positive correlations between neonatal and maternal 25-OH Vitamin D serum levels are present and they are negatively correlated with all sepsis markers. They can be sensitive early predictors for early onset sepsis in neonates.